Controlling the dimension of the quantum resonance in CdTe quantum dot superlattices fabricated via layer-by-layer assembly - TaeGi Lee (Nature Portfolio, 2020)
Designing quantum dot superlattices remains a challenge. Here, the authors present CdTe quantum dot superlattices via the layer-by-layer assembly and verify the miniband formation by measuring the excitation energy the dependence of the photoluminescence spectra and the detection energy dependence of the excitation spectra.